(untitled) (Fiep Bulletin - online, 2016)
Taxi drivers in Brazil workloads have very extensive work and during most of the time, remain in static positions. Based on this statement it can be said that these professionals are very prone to health problems and muscle pain. Considering these issues, this paper aims to conduct an ergonomic analysis on taxi drivers, accompanying their day to day in the city of Curitiba. Thus, was developed and implemented a simple questionnaire and objective, focused on ergonomics and health as a whole as well as the diagram Regions sore was used to lift the body parts that they felt pain for 30 taxi drivers working around central city. The interviews were made with these professionals in their working environments during their "services". The results showed worrisome data, for example that most of these workers have daily back pain and leg, high levels of stress, obesity, among other problems. We conclude therefore that before it becomes necessary to implement the guidelines, conducted by health professionals in order to correct the postures and the improvement of the general health of these workers while performing their activities programs.